Polymorphospora lycopeni A560, a new strain capable of producing lycopene, and its optimal fermentation and extraction conditions - Duan, Xiaomin; Li, Shilong; Li, Yan; Yang, Zihao; Zhang, Xiumin (Frontiers in Microbiology, 2026)
BackgroundLycopene, a vital antioxidant, can reduce oxidative damage to cells caused by reactive oxygen, prevent cancer, lower blood cholesterol levels, and mitigate cardiovascular diseases. We screened a lycopene-producing strain of the genus Polymorphospora, designated A560, and discovered that its metabolic pathway lacks the lycopene β-cyclase gene crtY, which is responsible for converting lycopene into β-carotene. The absence of crtY alleviates the challenges associated with the addition of a cyclooxygenase inhibitor, which previously hindered the large-scale accumulation of lycopene in Blakeslea trispora.MethodThis study was conducted to enhance lycopene production in strain A560 through a multi-stage optimization strategy, focusing on improving extraction efficiency and optimizing culture medium components. The extraction conditions were optimized by testing different solvent systems (acetone/n-hexane/ethanol), extraction temperatures, and durations. Subsequently, a uniform design (UD) was applied to systematically optimize the composition of the culture medium to maximize lycopene yield.ResultsThe extraction conditions were systematically optimized. A crushing duration of 4 min was identified as optimal for complete cell disruption. The most efficient solvent system was determined to be n-hexane/ethanol (2:1, v/v) at 60 °C, which yielded 62.05 ± 4.68 mg/L of lycopene—a 37.13% increase over extraction with acetone at room temperature (45.25 ± 0.98 mg/L). Subsequent medium optimization through a uniform design revealed that soluble starch and glycerol were critical components. Cultivation in the theoretically optimized medium predicted by the model resulted in a lycopene yield of 142.54 ± 8.58 mg/L. Finally, regulating the oxygen supply by adjusting the flask’s volume of air to a medium volume (Va/Vm) ratio proved crucial. The highest lycopene production of 201.44 ± 6.23 mg/L was achieved at a Va/Vm ratio of 1.5, which marks a 224.64% improvement over the yield obtained after the initial extraction optimization (62.05 ± 4.68 mg/L).ConclusionThe extraction and fermentation processes for lycopene production in Polymorphospora sp. A560 were successfully optimized, resulting in significantly enhanced yields. These results demonstrate that strain A560 is a promising microbial resource for the fermentative production of lycopene.